Safe-by-design development of a topical patch for drug delivery - Mafalda. B. Vaz; Carla Vitorino; João J. S. Sousa (Universidade de São Paulo, 2021)
Few topical products have been developed specifically to treat acute and chronic arthritis and inflammation, using non-steroidal anti-inflammatory drugs (NSAIDs). The lack of dosing accuracy commonly found in locally applied semisolid products for cutaneous use is a critical issue that leads to treatment failure. The aim of the present work is to develop a differentiated and innovative topical patch based on a monolithic hydrogel for ibuprofen skin delivery, in order to provide a safer and accurate way of drug administration along with improved treatment compliance. Topical patches based on hydroxypropylmethylcellulose (HPMC) were optimized in composition, in terms of enhancer and adhesive, supported on a systematic assessment of in vitro release and permeation behavior and adhesion properties. Several mathematical models were used to scrutinize the release mechanisms from the patches. In vitro release kinetics was shown to be mainly driven by diffusion. However, other mechanisms seemed to be also present, supporting the feasibility of using patches for sustained drug delivery. PEG 200 provided the best permeation rate, with a permeation enhancement ratio of ca. 3 times higher, than the commercial reference. The addition of Eudragit L30D 55 to the formulation led to the best adhesion profile, thus achieving a successful development based on a safe-by-design concept.